THE INFLUENCE OF EMOTIONAL INTELLIGENCE ON LEARNING MOTIVATION AND ITS IMPLICATIONS ON STUDENT LEARNING OUTCOMES IN THE SUBJECT OF ECONOMICS: (A Survey on Grade X Social Science Students at SMAN 3 Tasikmalaya) - Suswandi, Alma Ghia Almanazh; Suherti, Heti; Gumilar, Gugum (Transpublika Publisher, 2023)
This study investigates the correlation between emotional intelligence, learning motivation, and academic performance among 10th-grade Social Science students at SMAN 3 Tasikmalaya in the subject of Economics. Employing a quantitative survey-based approach with an explanatory survey research design, the research involves 107 students, using a saturated sample collection technique encompassing the entire population. Data was gathered through questionnaires, and statistical path analysis was utilized to explore both direct and indirect hypotheses. The findings revealed high scores in Learning Outcomes (6.997), Emotional Intelligence (5.395), and Learning Motivation (5.374). The direct hypothesis analysis demonstrates a significant influence of Emotional Intelligence on Learning Motivation and Learning Outcomes, while Learning Motivation alone does not significantly impact Learning Outcomes. Moreover, the indirect hypothesis analysis suggests that Emotional Intelligence does not exert a significant indirect effect on Learning Outcomes through Learning Motivation. This study sheds light on the significance of Emotional Intelligence in fostering Learning Motivation and subsequently impacting academic performance in Economics among high school students.